Detection and Diagnosis of Breast Cancer using Machine Learning Algorithm - J. Rakesh Reddy, G. Bindu Madhavi (International Journal of Advanced Science and Technology, 2019)
As indicated by Breast Cancer Institute (BCI), Breast Cancer is one of the most risky kind deadly disease that is extremely found in Females. According to clinical master identifying this disease in its first stage helps in living longer life. For identifying breast cancer mostly machine learning methods are used. In this paper we proposed Artificial neural network(ANN) approach for diagnosed breast cancer using Wisconsin Breast Cancer database. The main focus of this work is to look at and clarify how ANN gives effective and better solution arrangement when its work with group AI calculations for diagnosing bosom malignant growth even the factors are decreased. In this paper we utilized the Wisconsin Diagnosis Breast Cancer dataset. When contrasted with related work from the writing. It is indicated that the ANN approach with calculated calculation is accomplished 99.00% precision from another AI calculation.